Georges Canguilhem y el estatuto epistemológico del concepto de salud Georges Canguilhem and the epistemological status of the concept of health - Sandra Caponi (História, Ciências, Saúde: Manguinhos, 1997)
Tomando como punto de partida la discusión de Canguilhem relativa al estatuto epistemológico del concepto de salud, pretendemos problematizar las conceptualizaciones dada por la OMS y una definición ampliada enunciada por la VIII Conferencia Nacional de Salud que se han convertido hoy en hegemónicas. Esas conceptualizaciones entienden la salud como equilibrio y adaptación al medio. Nuestro objetivo fundamental es evidenciar que el ámbito de los enunciados está en permanente cruzamiento con el ámbito de lo no discursivo, de lo institucional. Siendo así, la aceptación de determinado concepto de salud implica el direccionamiento de determinadas políticas y de ciertas intervenciones efectivas sobre el cuerpo y la vida de los sujetos. Taking as a point of departure Canguilhem's view on the epistemological status of the concept of health, the article examines current hegemonic concepts which see health as a question of balance and adjustment to the environment-including herein the conceptualization posed by the World Health Organization and the broad definition laid out during the 8th Health Conference. The basic goal of this examination is to show that what is defined in discursive statements constitutes an ongoing interaction with the metadiscursive statements more closely related to the world of institutions and institutional action. It is therefore argued that the adoption of a particular notion of health implies the selection of a particular direction in health care policies as well as the application of a particular set of intervention strategies regarding the lives and bodies of subjects.